Optimalisasi Penggunaan Media Sosial Sebagai Promosi Desa Wisata Di Lembang Randanan Kecamatan Megkendek Kabupaten Tana Toraja - Jesika Palengka; Yustin Toding Silambi; Dwibin Kannapadang; Ellyn Pata’dungan (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Information and digital technology has become an important part of an organization to grow and develop in an era of change. This will show how tourist villages use information and digital technology to provide new information, services and value to a wide audience. One of the tourist attractions in Lembanga Randanan is the Painted Rice Fields. The fertile rice fields provide beautiful landscapes and a deep impression. Students from the Management study program at the UKI Toraja Faculty of Economics with the theme Tourism Village are collaborating with the Lembang community and parties in the development and promotion of the Painted Rice Fields tourism in Lembang Randanan so that it can be touched by a wide audience, especially the commercialization of tourism. From the results of observations, it was found that the basic problems that hinder tourism promotion are the lack of public awareness to promote painted rice field tourism and the ineffective use of information and digital technology. The aims and objectives of organizing community service are to introduce painted rice field tourism to the general public and to help the Lembang Randanan community in using information and digital technology for promotion. This research was conducted using a qualitative descriptive research method with primary data collection techniques in the form of observation, interviews and documentation, while secondary data collection was obtained from searching various references such as books, journals and articles. The results of the service activities that have been carried out are helping tourist villages with promotion, marketing and management of tourist villages. This includes creating Instagram and YouTube social media accounts which aim to promote tourist villages, especially painted rice field tourism in Lembang Randanan. From this research, it is hoped that potential-based tourism village promotion can be carried out.